(untitled) (Research, Society and Development, 2021)
The human being becomes involved in the work of God, through science, the presence and the power of each person, in this sense, these elements predict the spirit of love with which the human being is ready to administer the work of God . Liability to the Creator is a founding element of human action, under this prospect it is shown that sharing precedes having and that science is presenting itself to God to realize the kingdom. The person’s science, presence and power will always be the fruit of love that happens in the relationship of respect for God’s creation. The proposal to narrate the human being, administrator and co-creator of the work of God, is based on the documents of the social doctrine of the Church and the documents that elucidate the life and experience of the family ‘family morals’. Knowledge, human science, is not done so that there are submissives and submissives, but, so that there is the fullness of human life according to the human capacity to manage the work of God.